The Role of Strategic Leadership in the Profitability of BRI Bank Work Units - Sulistiyarso, Heru; Zulmi, Wiltomi Berkat; Raharjo, Susilo Toto (LifeSciFi, 2024)
This study aims to analyse the role of the BRI Bank Branch Office Head's leadership strategy in influencing the profitability of the work units they lead, with a focus on the BRI Jakarta Regional Office. Facing the challenges of tight competition in the banking industry, leadership strategy at the branch level is a key factor in achieving profit targets and business desires. Through a qualitative approach with a case study method, this study collected data through in-depth interviews and document analysis from several Branch Offices in Jakarta. The results of the study indicate that adaptive leadership, team management skills, and understanding of local market conditions are important elements in maintaining Branch profitability. These findings are expected to provide insight into the development of leadership strategies in the Indonesian banking sector, especially in improving the effectiveness of Branch leaders in achieving financial organization targets.